Whiskey in a Teacup - Witherspoon, Witherspoon, Reese (London Simon & Schuster, 2018)
A beautifully designed, deluxe edition of Whiskey in a Teacup signed by the author, including a monogrammed slipcover box, extra material, and ribbon marker$1 (Bthe perfect gift for fans of Reese Witherspoon. s
Include Color Illustrations and Tables
Keywords: a